Pengaruh Budaya Organisasi dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan PT. Semen Indonesia (Persero) Tbk Gresik - BUDI PRAMUDIANTO, EKYAN (Jurnal Ilmu Manajemen (JIM), 2018)
Management of human resources very play an important role in managing the source of human resources (HR) to companies to the utmost to to reach vision and mission company. For the company, employees is the main pillar in increase the company performance. Therefore, the company put appreciation of the award allegiance this working over devotion employees over this help enlarging an enterprise until now. The influence of culture organization and workplace physical is one of the picture show the extent to which employee performance could be achieved based on the purpose PT Semen Indonesia (Persero) Tbk Gresik. The organization and physical work environment simultaneously significant impact on employee performance and have become important on the performance of an employee at PT Semen Indonesia (Persero) Tbk Gresik. Keywords: organization culture, physical work environment, employee performance